Numerical and experimental studies of the Braga Sports Stadium suspended roof - Elsa Caetano (2005)
This paper describes a set of dynamic numerical and experimental studies conducted on the suspended roof of the Braga Municipal Sports Stadium. Modal parameters, calculated from a numerical model of the constructed structure that takes into account the geometrically nonlinear structural behaviour and the progressive application of loads, are compared with the corresponding parameters identified on the basis of an ambient vibration test. Particular attention is given to modal damping identification due to the necessity of analysing the susceptibility of the suspended roof to buffeting effects.